Chemoselective Labeling and Immobilization of Phosphopeptides with Phosphorimidazolide Reagents. (26th October 2022) - Brown, Nathaniel W.; Schlomach, Sandra K.; Marmelstein, Alan M.; Fiedler, Dorothea
Abstract: Protein phosphorylation is one of the most ubiquitous post‐translational modifications, regulating numerous essential processes in cells. Accordingly, the large‐scale annotation of phosphorylation sites continues to provide central insight into the regulation of signaling networks. The global analysis of the phosphoproteome typically relies on mass spectrometry analysis of phosphopeptides, with an enrichment step necessary due to the sub‐stoichiometric nature of phosphorylation. Several affinity‐based methods and chemical modification strategies have been developed to date, but the choice of enrichment method can have a considerable impact on the results. Here, we show that a biotinylated, photo‐cleavable phosphorimidazolide reagent permits the immobilization and subsequent cleavage of phosphopeptides. The method is capable of the capture and release of phosphopeptides of varying characteristics, and this mild and selective strategy expands the current repertoire for phosphopeptide chemical modification with the potential to enrich and identify new phosphorylation sites in the future. Abstract : Phosphorimidazolide reagents react selectively with phosphoryl groups. Using a biotinylated, photocleavable phosphorimidazolide reagent a method was established for capture and release of phosphopeptides which has the potential to mildly and selectively enrich phosphopeptides in biological samples.